Perbedaan Kandungan Vitamin C Dan Serat Kasar Pada Jus Jeruk Siam Banjar (Citrus Nobilis Var. Microcarpa) Yang Diolah Menggunakan Berbagai Alat Pengolahan Jus - Nany Suryani; Rissa Saputri; Hanan Hanan; STIKES Husada Borneo; Alumni STIKES Husada Borneo (Jurnal Kesehatan Indonesia, 2014)
Juice is the alternative material of healing and to fulfill nutrient. Orange juices is most often available where ever, either in cafÃ©, restaurant or hotel. Orange juice is also easy to make. Citrus fruits are famous rich in vitamin C and fiber. Vitamin C and fiber are the nutrients that have many roles in maintaining a healthy body. There are 3 way to make a juice, such as Squeezing, use Blenders and Juicers. The third equipment has a different way of working in which ways of working of each juice processing devices have the potential to result in reduced content of vitamin C and fiber in the juice produced. This study uses orange Siam Banjar. The research goal is to determine the content of vitamin C and crude fiber in each juice is processed using a variety of juice processing equipment, as well as to determine whether there is a difference in vitamin C and crude fiber in the juice produced in order to process the juice with vitamin C and knowing enough juice processing equipment that produces juice with vitamin C and fiber content of most rough. The content of vitamin C was analyzed using Iodimetri while crude fiber method using a gravimetric method. Based on the results of the ANOVA test vitamin C showed p <Î± is the difference between the vitamin C content of the juices. Juice has the highest content of vitamin C found in processed juice using Juicer. The juice has 11,264 of vitamin C. ANOVA test results showed crude fiber p <Î± it is mean the difference between the crude fiber content of the juices. Juice which has the highest crude fiber content is juice processed using Blender. The juice has 6,320% of crude fiber.